2017
DOI: 10.1007/s11154-017-9423-2
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D, sub-inflammation and insulin resistance. A window on a potential role for the interaction between bone and glucose metabolism

Abstract: Vitamin D is a key hormone involved in the regulation of calcium/phosphorous balance and recently it has been implicated in the pathogenesis of sub-inflammation, insulin resistance and obesity. The two main forms of vitamin D are cholecalciferol (Vitamin D3) and ergocalciferol (Vitamin D2): the active form (1,25-dihydroxyvitamin D) is the result of two hydroxylations that take place in liver, kidney, pancreas and immune cells. Vitamin D increases the production of some anti-inflammatory cytokines and reduces t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
95
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 111 publications
(101 citation statements)
references
References 145 publications
4
95
0
2
Order By: Relevance
“…Celulele β-pancreatice suferă modificări, conducând la eliberarea unor cantități mari de insulină, hiperinsulinemia instalată va determina apariția DZ2 în procent de 60% [18][19][20]. Rezistența la insulină este strâns corelată cu obezitatea, care, la rândul ei, este asociată cu stresul oxidativ și un nivel inflamator crescut [18,21]. Deficiența de vitamină D poate fi implicată în patogeneza dezechilibrelor metabolice care determină instalarea hiperglicemiei și a obezității [22].…”
Section: Roluri Fiziologice Ale Vitaminei Dunclassified
“…Celulele β-pancreatice suferă modificări, conducând la eliberarea unor cantități mari de insulină, hiperinsulinemia instalată va determina apariția DZ2 în procent de 60% [18][19][20]. Rezistența la insulină este strâns corelată cu obezitatea, care, la rândul ei, este asociată cu stresul oxidativ și un nivel inflamator crescut [18,21]. Deficiența de vitamină D poate fi implicată în patogeneza dezechilibrelor metabolice care determină instalarea hiperglicemiei și a obezității [22].…”
Section: Roluri Fiziologice Ale Vitaminei Dunclassified
“…Recent studies have shown that high vitamin D status offers protection against T2DM. Vitamin D has important biological functions including modifying insulin secretion and refining insulin resistance [3]. It is a hormone precursor and it has been found to be associated with various metabolic disorders [4].…”
Section: Introductionmentioning
confidence: 99%
“…Preliminary findings have suggested that vitamin D supplementation may improve cognition in schizophrenia , however the association of hypovitaminosis D with cognitive impairment has not been explored to date. Vitamin D insufficiency has been associated with metabolic syndrome in psychotic disorders (Yoo et al, 2018), with insulin resistance (Garbossa and Folli, 2017), with thyroid dysfunction (Kim, 2017;Wang et al, 2018) and high vitamin D blood levels have been suggested to reduce peripheral low-grade inflammation (Zhu et al, 2015). There is a current debate on the association between alcohol use disorder and vitamin D deficiency (Tardelli et al, 2017).…”
Section: Introductionmentioning
confidence: 99%